Mexico : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Mexico's Arrangement Under the Flexible Credit Line (FCL) and Cancellation of Current Arrangement. Mexico continues to face significant uncertainty regarding the pace and outcome of the negotiations on the North American Free Trade Agreement. The authorities are requesting a two-year precautionary FCL arrangement and the cancellation of the current arrangement, approved on May 27, 2016. They consider that, in an environment where external risks affecting Mexico remain elevated, an FCL arrangement in the requested amount will play a critical role in supporting their overall macroeconomic strategy, preserving investor confidence, and providing insurance against tail risks. The IMF staff supports the authorities' request.